Larvae of three East-Asian species of Nemoura (Plecoptera: Nemouridae) - Teslenko, Valentina A. (Zootaxa, 2017)
Larvae of the three East-Asian Nemoura species, N. jezoensis (Okamoto), N. manchuriana Ueno and N. nigrodentata Zhiltzova are described and illustrated in detail for the first time. Descriptions for the male and female of N. nigrodentata are supplemented.